Incidence and long-term patient reported outcome measures of patients with radiological cauda equina compression but without clinical features of cauda equina syndrome - Hamzah Alsheikh Soleiman; Mary Solou; Andreas K. Demetriades (Journal of Craniovertebral Junction and Spine)
Background: Cauda equina syndrome (CES) is a rare spinal emergency. Paradoxically, in the British NHS, suspected CES requiring an emergency magnetic resonance imaging constitutes one of the commonest reasons for acute referrals to neurosurgery/spine surgery. Further acute referrals also occur with the reverse scenario, when radiological evidence of cauda equina compression is not accompanied by the clinical red flags of the syndrome. The understanding of CES, particularly in cases with radiological compression but lacking clinical symptoms, remains limited. This study aims to explore the incidence and the long-term outcomes of such patients, addressing a significant knowledge gap. Methods: A single-center, retrospective and cohort study was conducted, analyzing suspected CES referrals managed between August 2013 and November 2014. Patients with radiological cauda equina compression but without clinical CES features were identified. A structured questionnaire assessed long-term patient reported outcomes. Results: Out of 344 suspected CES referrals, 38 patients (11%) had radiological CES of degenerative cause without clinical symptoms. From those with radiological cauda equina compression but no features of CES, 14 were assessed for long-term results and the majority still underwent surgery (64%), either emergent (35.7%) or elective (28.6%). The long-term patient reported outcomes of the operated patients revealed that 66.7% were fully ambulant, 77.8% maintained an intact sexual function, and 88.9% were free of urinary symptoms. However, no matter the management, chronic pain persisted in 85.7%. Conclusion: This study highlights the existence of patients who are referred urgently with radiological cauda equina compression but who lack clinical CES symptoms. Despite surgical interventions, chronic pain remains a significant issue. Further research, including multi-centered studies, is warranted to enhance our understanding of this condition and its nuanced subpopulations.